1996
DOI: 10.1139/z96-232
|View full text |Cite
|
Sign up to set email alerts
|

Survival of breeding male American woodcock in Maine

Abstract: We radio-marked 150 male American woodcock (Scolopax minor) during 1987–1989 and estimated period survival for 1 April – 15 June. Survival varied from 0.690 (1989) to 0.924 (1988), with a 3-year mean (95% confidence interval) of 0.789 (0.693–0.885). Woodcock were killed by raptors (n = 14, 53.8%), mammals (n = 1, 3.8%), or unknown predators (n = 5, 19.2%); six deaths (23.1%) were from miscellaneous causes, including three (11.5%) from entanglement in the transmitter harness. A composite survival estimate based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 16 publications
1
34
0
Order By: Relevance
“…), seasonal survival from radio telemetry (Longcore et al. ), harvest surveys (Padding et al. ), and band‐recovery analyses (Krementz et al.…”
Section: Introductionmentioning
confidence: 99%
“…), seasonal survival from radio telemetry (Longcore et al. ), harvest surveys (Padding et al. ), and band‐recovery analyses (Krementz et al.…”
Section: Introductionmentioning
confidence: 99%
“…We found no sex or age‐related differences in woodcock survival rates during fall. Similarly, no sex or age‐related variation has been found in most telemetry‐based studies of woodcock survival (Krementz et al , Longcore et al , Krementz and Berdeen , Longcore et al , McAuley et al ) during various parts of the year. An exception was Derleth and Sepik (), who found that summer‐fall survival rate estimates were related to age.…”
Section: Discussionmentioning
confidence: 98%
“…Data from the Harvest Information Program suggest that most woodcock hunting mortality occurs in breeding ground states (Cooper and Rau ). Woodcock survival rates have been documented with radiotelemetry during various periods of the year (e.g., Derleth and Sepik ; Krementz et al ; Longcore et al , ) but only McAuley et al () examined survival in a hunted population during fall, and their study was conducted in the Eastern Region. Thus, information on survival during fall is lacking for the Central Region.…”
mentioning
confidence: 99%
“…If survival is <1 between the banding and the recovery periods, thenf is underestimated because it is confounded with survival during those periods. Radio-telemetry estimates of winter and spring survival probabilities for woodcock are relatively low ( S 25 December to 7 February ¼ 0:72, Krementz and Berdeen (1997); S 1 April to 15 June ¼ 0:79, Longcore et al (1996)) compared with summer and early fall ( S June to October > 0:894, Derleth and Sepik (1990)). Therefore, survival of birds banded in July and August is likely to be~1, but survival of birds banded in other months is likely to be <1, so that the model of Brownie et al (1985) is likely to underestimate f. Thus, to minimise bias and include as many bandings as possible, we included two groups of banded woodcock for estimating f age,t .…”
Section: Band-recovery Modelmentioning
confidence: 99%